Masalah dan Solusi Model Pengembangan Pembiayaan Pertanian dari Aspek Keuangan Syari’ah - Sri Maulida; Ahmad Yunani (Universitas Muhammadiyah Magelang, 2017)
This study aims to discuss the problems and solutions in terms of sharia financial aspects of the development of agricultural financing. This study used multiple linear regression analysis with ordinary least square method (OLS) combined with a descriptive explorative approach and developed by using literature review approach or literature study. The theory or conceptual approach is done by referring from several sources, such as books, scientific journals, and the internet. All existing idea descriptions are combined into a single frame of thought. The results showed that the variable of problem financing in agriculture sector had a significant negative effect on the profitability of sharia banking, therefore the application of financing concept for farmers through Sharia Finance Cooperative or Baitul Maal bi Tamwil (BMT) using Bai 'Salam